Improving Services in a hybrid academic library System (2021)
The mixture of traditional or manual ways of carrying out library operations with new, modern, automated systems often brings about several problems. The problems are ones that can be tackled within the framework of having appropriate systems dynamics routines applied and also making use of personnel skilled in strategic management of hybrid library systems. The paper describes a hybrid academic library system and draws up a model of this system suggesting strategies and scenarios for achieving optimum performance of the system in a technology changing world. A system dynamics model for the management of the system is developed around the issues of personnel management, collection management, capacity building, and provision of access to research materials, Information Technology (IT) infrastructure, forming of Consortia, and Security in the system. Recommendations are made as to which strategy/ scenario or combinations of scenarios will provide lasting solutions to the problems recurring or likely to reoccur in a hybrid academic library system.